PROSEDUR PELAYANAN PRODUK TABUNGAN PADA PT. BPR INSUMO SUMBER ARTO - Kusuma, Hendra (Universitas Pawyatan Daha, 2022)
This study aims to determine the procedure for saving and deposit product services carried out by PT. BPR Insumo Sumberarto. These savings product services include opening, depositing, withdrawing and closing customer savings accounts. In addition, this study aims to determine the calculation of interest on savings at PT. BPR Insumo Sumberarto. Based on the results of the discussion, it is concluded that the service procedures performed by PT. BPR Insumo Sumberarto is good and according to procedures. Calculation of interest on savings made by PT. BPR Insumo Sumberarto is conducted every day. However, the recording in the customer's savings book is carried out at the end of each month. Based on the conclusions, it can be suggested that PT. BPR Insumo Sumberarto provided brochures on the procedure for servicing savings products at the BPR. In calculating interest on savings that apply to PT. BPR Insumo Sumberarto. preferably the information on the interest rate applied to the BPR is included in a statement in the customer's savings account book.